2016
DOI: 10.1007/s00424-016-1925-3
|View full text |Cite
|
Sign up to set email alerts
|

Profound hypothermia after adenosine kinase inhibition in A1AR-deficient mice suggests a receptor-independent effect of intracellular adenosine

Abstract: Administration of the nucleoside adenosine has been shown to induce hypothermia in a number of species, an effect mediated predominantly by the adenosine 1 receptor (A1AR) subtype. The present experiments were performed to explore the possibility that the rise of intracellular adenosine levels expected to accompany adenosine administration may contribute to the hypothermic effect of adenosine independent of A1AR activation. Since phosphorylation of adenosine by adenosine kinase (ADK) is causal in the maintenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
1
9
1
Order By: Relevance
“…Adenosine kinase phosphorylates adenosine to AMP, keeping intracellular adenosine levels low, thereby drawing extracellular adenosine into cells down its concentration gradient. It has been suggested that inhibition of adenosine kinase causes hypothermia via AR-independent mechanisms [38]. We confirmed that treatment of wild-type mice with the adenosine kinase inhibitor A134974 [39] caused hypothermia in a dose-dependent manner (Fig 5A–5D).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Adenosine kinase phosphorylates adenosine to AMP, keeping intracellular adenosine levels low, thereby drawing extracellular adenosine into cells down its concentration gradient. It has been suggested that inhibition of adenosine kinase causes hypothermia via AR-independent mechanisms [38]. We confirmed that treatment of wild-type mice with the adenosine kinase inhibitor A134974 [39] caused hypothermia in a dose-dependent manner (Fig 5A–5D).…”
Section: Resultssupporting
confidence: 85%
“…In contrast, the QKO mice demonstrate that the acute hypothermia caused by an adenosine kinase inhibitor is completely attributable to ARs. Some of the hypothermia is due to the increased extracellular adenosine activating A 1 AR [38]. While possible explanations for the remaining A134974-induced hypothermia have been proposed, the QKO results dictate that the non–A 1 AR-mediated hypothermia must occur via A 2A AR, A 2B AR, and/or A 3 AR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, fasting-induced torpor in mice does not require any of these receptors, but the mechanism remains unknown [ 20 ]. Eisner et al [ 24 ] demonstrate that treating mice with Ado or AdoK inhibitors (thus obtaining an increase of Ado) causes a profound hypothermia lasting longer if caused by AdoK inhibitors. The same experiment performed in A1AR −/− mice caused a less pronounced effect that is 40–60% of that observed in wild type mice.…”
Section: Hypothermia Induced By Adenylate Compoundsmentioning
confidence: 99%
“…Furthermore, ADA inhibitors are unable to induce hypothermia and do not affect the hypothermic effect of AdoK inhibitors on both wild type and A1AR −/− mice, thus indicating that the deamination of Ado is not required for the nucleoside to induce hypothermia. The authors conclude that hypothermia induced by Ado in mice is a combined response to a receptor-mediated (mainly A1-mediated) mechanism and to a still-unknown intracellular mechanism in which AdoK plays a fundamental regulatory role [ 24 ].…”
Section: Hypothermia Induced By Adenylate Compoundsmentioning
confidence: 99%